2016
DOI: 10.12659/msm.897759
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Levels and Uric Acid/Creatinine Ratios in Stable Chronic Obstructive Pulmonary Disease (COPD) Patients: Are These Parameters Efficient Predictors of Patients at Risk for Exacerbation and/or Severity of Disease?

Abstract: BackgroundSerum uric acid (sUA) levels were previously found to be correlated with hypoxic states. We aimed to determine the levels of sUA and sUA/creatinine ratios in stable COPD patients and to evaluate whether sUA level and sUA/creatinine ratio can be used as predictors of exacerbation risk and disease severity.Material/MethodsThis cross-sectional study included stable COPD patients and healthy controls. The sUA levels and sUA/creatinine ratios in each group were evaluated and their correlations with the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 21 publications
1
45
0
1
Order By: Relevance
“…A total of 20 articles were retrieved for full-length article review and 12 articles were excluded at this stage as they did not report the level of serum uric acid among participants with and without COPD. Finally, eight studies [12][13][14][15][16][17][18][19] with 1,612 participants were eligible for the meta-analysis. The literature retrieval, review and selection process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 20 articles were retrieved for full-length article review and 12 articles were excluded at this stage as they did not report the level of serum uric acid among participants with and without COPD. Finally, eight studies [12][13][14][15][16][17][18][19] with 1,612 participants were eligible for the meta-analysis. The literature retrieval, review and selection process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The increased level of serum uric acid is thought www.journals.viamedica.pl to be a consequence of increased purine catabolism in the presence of tissue hypoxia [11]. The current systematic review and meta-analysis was conducted to compare serum uric acid level between patients with COPD, a common hypoxemic disorder, and individuals without COPD [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Uric acid elimination occurs mainly in urine, which is dependent on renal function. Previous studies have used uric acid to creatinine ratio as a surrogate marker to investigate the relationship between uric acid and other outcomes of interest, and it is a better predictor of incident chronic kidney dysfunction than uric acid alone . These studies highlight the advantage of implementing uric acid to creatinine ratio as it more precisely reflects the endogenic uric acid production.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is a terminal product of purine degradation, and high levels of circulating uric acid have been associated with gout, type 2 diabetes (T2D), and renal and cardiovascular diseases [1]. Recently, a higher serum uric acid (SUA) to creatinine ratio was associated with an increased risk of metabolic syndrome [2], and predicted chronic kidney disease incidence in T2D patients [3] and chronic obstructive pulmonary disease as compared to uric acid alone [4]. Growing evidence also suggests that elevated SUA levels are frequently identified in patients with obstructive sleep apnea [5], possibly due to elevations in catecholamine levels [6] and intermittent hypoxia.…”
Section: Introductionmentioning
confidence: 99%